2016
DOI: 10.1080/21582041.2016.1138502
|View full text |Cite|
|
Sign up to set email alerts
|

How well can we predict educational outcomes? Examining the roles of cognitive ability and social position in educational attainment

Abstract: Social inequalities in UK educational outcomes continue to persist despite improvements in recent years. However, studies that examine these inequalities fail to account for differences in prior cognitive ability. We seek to determine the influence of cognitive ability on educational outcomes and the extent of socio-economic disparities in education across a wide range of indicators while accounting for cognitive ability. Social inequalities exist whereby children from disadvantaged backgrounds systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…There was a large amount of overlap in the polygenic score distribution between pupils in the top 10% of attainers and all others; while pupils with a high polygenic score are more likely to be high attainers, genetics do not determine high attainment. High academic attainment is due to both environmental and genetic factors, including social background 19 , teacher bias 22,23 , the home and school environment 24,25 , and luck. It is also possible that the quality of family and school environments may constrain or support pupils' ability to exploit their genetic propensity to education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a large amount of overlap in the polygenic score distribution between pupils in the top 10% of attainers and all others; while pupils with a high polygenic score are more likely to be high attainers, genetics do not determine high attainment. High academic attainment is due to both environmental and genetic factors, including social background 19 , teacher bias 22,23 , the home and school environment 24,25 , and luck. It is also possible that the quality of family and school environments may constrain or support pupils' ability to exploit their genetic propensity to education.…”
Section: Discussionmentioning
confidence: 99%
“…For polygenic scores to be informative for personalised education and provide actionable information to inform effective policy, the scores must not only explain sufficient variation in educational attainment, but they must also explain sufficient variation over and above other readily available phenotypic data. Phenotypic measures that are predictive of educational attainment such as sex, month of birth and prior attainment 17,18 are readily available to schools while others measures such as parental education and socioeconomic position 19,20 are easily and cheaply collected. However, to date, few studies have investigated how well polygenic scores predict individual level educational attainment conditional on observable phenotypes that are easily available to educators.…”
Section: Introductionmentioning
confidence: 99%
“…25 That genetic correlations between educational attainment and cognitive ability persist so strongly throughout childhood further demonstrates the importance of cognitive ability to education in the UK. 8 Further research is required to investigate how these genetic relationships persist into further and higher education. Bivariate heritability analyses indicated that shared genetic variation can explain a substantial fraction of the phenotypic correlations between educational attainment, SEP and cognitive ability.…”
Section: Negative Confoundingmentioning
confidence: 99%
“…A persons own educational attainment and their parents occupational position are two of the strongest determinants of health and social outcomes throughout the lifecourse. [1][2][3][4][5] Education and occupational position are conceptually viewed as subcategories of broader socioeconomic position (SEP), 6,7 are strongly correlated [8][9][10] and highly heritable. 2,5,[11][12][13] Furthermore, education has been demonstrated to have a complex genetic architecture characterised by high polygenicity, 14,15 and this is likely to be the case for other complex social traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation